Peer today, boss tomorrow [videorecording] - 353286 Screnci, Joe (Sydney, Australia : Mind Resources, 2005)
Help newly promoted supervisors navigate their changing roles and have immediate impact with Peer Today, Boss Tomorrow. Key strategies, hands-on workshop activities and practical suggestions make this program an excellent choice for organizations that promote from within or train new supervisors regularly. Learning Point Highlights: --- Honestly reflects the mixed feelings involved in moving from peer to boss --- Outlines 4 strategies to help new managers make successful transitions --- Helps new managers address their evolving relationships with colleagues. Workshop Outcomes & Self Study Objectives --- Explain the role of the supervisor --- State how the role of the supervisor is different from that of a non-manager employee --- Navigate your changing role by applying 4 strategies to help you make the transition from peer to boss. Source : Mind Resources webpage (http://www.mindresources.net).